Selection, effective dominance, and completeness of Cry1A.105/Cry2Ab2 dual-protein resistance in Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) - Tiago SILVA; Ying NIU; Tyler TOWLES; Sebe BROWN; Graham P. HEAD; Wade WALKER; Fangneng HUANG (Journal of Integrative Agriculture, 2023)
In the U.S., Helicoverpa zea (Boddie) is a major pest targeted by both transgenic maize and cotton expressing Bacillus thuringiensis (Bt) proteins. Resistance of insect to Bt maize and cotton containing cry1A and cry2A genes has widely occurred in the U.S. In this study, two trials were performed to investigate larval survival and development of a Cry1A.105/Cry2Ab2 dual-protein resistant (VT2P-RR), a susceptible, and an F1 heterozygous (VT2P-RS) populations of H. zea on ears of nine Bt and three non-Bt maize hybrids. The Bt maize hybrids evaluated represent five common pyramided traits expressing two or three of the Cry1A.105, Cry1Ab, Cry1F, Cry2Ab2, and Vip3Aa20 proteins. In the laboratory, neonates of the three H. zea populations were inoculated on silks of ears collected from maize at R1–R2 plant stages; and larval survivorship was checked 10 d after neonate release. All three insect populations survived normally on non-Bt maize ears. Varied numbers of VT2P-RR and VT2P-RS survived on ears of Cry1A.105/Cry2Ab2 maize, while all larvae of the three populations died or could not develop on ears of Vip3Aa20-expressing maize. The results demonstrated that the dual-protein resistant H. zea was not cross-resistant to Vip3Aa20-expressing maize, and thus traits with vip3Aa20 gene should be effective to manage Cry1A.105/Cry2Ab2-resistant H. zea. The resistance in VT2P-RR was determined to be incomplete on Cry1A.105/Cry2Ab2 maize. The effective dominance levels varied greatly, from recessive to incompletely dominant, depending on maize hybrids and trials, suggesting that proper selection of maize hybrids could be important for mitigating the Cry1A.105/Cry2Ab2 resistance. The data generated should aid in modeling multiple-protein Bt resistance in H. zea.